(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Palshkova I. The formation of professional and pedagogical culture of the future teacher’s approach kompetentnosny. In article formation possibilities professionally – pedagogical culture of future teachers of elementary school are opened by means of a kompetentnosny approach. The professional and pedagogical culture is a difficult dynamic process of gradual formation of professional knowledge, professional abilities and professionally meaning qualities of the personality. Kompetentnosny an approach assists professional formation of the identity of future teacher.